Keeping your distance: attentional withdrawal in individuals who show physiological signs of social discomfort. - Szpak, A; Loetscher, T; Churches, O; Thomas, N; Spence, C; Nicholls, M (2014)
Being in close social proximity to a stranger is generally perceived to be an uncomfortable experience, which most people seek to avoid. In circumstances where crowding is unavoidable, however, people may seek to withdraw their attention from the other person. This study examined whether social discomfort, as indexed by electrodermal activity, is related to a withdrawal of attention in 28 (m=8, f=20) university students. Students performed a radial line bisection task while alone or together with a stranger facing them. Physiological arousal was indexed by a wrist monitor, which recorded electrodermal activity. Correlational analyses showed that individuals who displayed physiological discomfort when together showed a withdrawal of the perceived midpoint of the line towards them (and away from the stranger). Conversely, individuals who showed no discomfort exhibited an expansion of the perceived midpoint away from them. We propose that participants shift their attention away from the stranger to increase interpersonal distance and reduce anxiety/arousal.